Internal Control Systems and Quality Service Delivery: A Case Study of Kabale Municipal Council. - Ahimbisibwe, Laban Isaac (Kabale University, 2024)
The study determined the effect of internal control on the quality of service delivery in Kabale Municipal Council (KMC). The purpose of the study was to establish the effect of internal control on quality of service delivery highlighting the various internal control systems, establishing the effect of internal control systems on the quality of service delivery as well as the challenges associated with the use of internal control systems in KMC. The variables of the study were internal control systems and service delivery. The study used a cross-sectional research design and simple random sampling, data was collected by the use of questionnaires which were supplemented by interview guides using a sample of 40 respondents. The collected data was analyzed using qualitative and quantitative methods where frequency and percentage tables as well as pie charts and graphs were used to determine the effect of internal control on quality of service delivery. The findings confirmed the existence of internal control systems in Kabale municipal council ascertained by the existence of strong segregation of duties, which ascertained preventive as well as directive internal control procedures. The research findings further showed that internal control has an effect on the quality of service delivery in KMC. Internal control showed a major effect on service delivery through segregation of duties, monitoring, and evaluation of performance, as well as having policies and procedures for effective communication and information flow. While it also highlighted the challenges associated with the use of internal control systems especially management override and poor information flow with ineffective communication and poor risk management procedures. In conclusion, the study ascertained that various internal control systems in KMC were based on the conclusion of ratings from the analyzed data. Internal control systems were confirmed to have a distinctive effect on the quality of service delivery in the municipal council despite the challenges that were identified to be associated with the use of those internal control systems. Recommendations encouraged that procurement personnel and accounting officers be given training on the need and value of having functional internal control systems as well as enabling other organizational members to adopt the currently available internal controls for effective and efficient service delivery while areas for further improvement suggested that research be carried out to in other public entities to determine how internal control affects service delivery.